Influence of the synthesis time in the textural and structural properties of Ni-Containing Mesoporous materials - Carraro, Paola María (2015)
MCM-41 materials have been synthesized by hydrothermal synthesis, and the influence of the synthesis time variation on the structural and textural properties of the final solids was studied. Nickel-modified samples were synthesized with a molar ratio Si/Ni of 60 and increased days of synthesis from 0 to 7 days. The structures obtained were characterized by X-ray diffraction (XRD) and UV-vis diffuse reflectance (UV–Vis DRS) spectroscopy. XRD patterns of samples are typical of MCM-41 structure, which improves with increasing the time of hydrothermal treatment. XRD and UV–vis studies revealed that the short synthesis times do not allow the proper incorporation of nickel in the structure. It was corroborated that, the synthesis time has an important influence on the properties of mesoporous material modified with Ni.